Professional Language Training of Students of International Relations: Didactics - E. V. Voevoda (Vestnik MGIMO-Universiteta)
The article addresses the theory of professional language training of students majoring in international relations. Showing the essence of competence-based professional education, the author offers definitions of content and purpose of language training and analyses its specific functions and properties.